Pilot-scale study on seeded precipitation assisted nanofiltration for flue-gas desulfurization wastewater softening. (18th January 2022) - Duan, Yawei; Zhong, Zhencheng; Tong, Zhenwei; Cheng, Zihong; Xiong, Rihua
Abstract: In order to reduce the cost of chemical softening, the seeded precipitation assisted nanofiltration (NF) process was introduced into zero liquid discharge (ZLD) of flue-gas desulfurization (FGD) wastewater treatment. A pilot-scale system was developed and run for 168 h in a coal-fired power plant. The system mainly consists of lime softening, ambient temperature crystallizer (ATC) and NF, in which the raw water treatment capacity was 1 m 3 /h. The results indicated that the system operated stably, the softening cost was 13.30 RMB/m 3, and the electricity cost was 3.39 RMB/m 3 for the FGD wastewater in this pilot system. High quality gypsum was got from the ATC unit, of which the purity was 95.8%. Through this system, the hardness removal rate was higher than 98.9% and the water recovery rate reached 96%. In addition, the pressure and permeate flux kept stable in the ultrafiltration (UF) unit and NF unit, indicating no scaling occurred in the two units during 168 h test. Thus, a feasible and cost-effective process was provided by using the seeded precipitation assisted NF to deal with the FGD wastewater. HIGHLIGHTS: Seeded precipitation assisted NF is introduced into ZLD process of FGD wastewater. The softening cost is 13.30 RMB/m 3 and much less than softening by Na2 CO3 . The hardness removal rate of this pilot system is higher than 98.9%. High quality gypsum was got from the ATC unit, of which the purity was 95.8%.